(untitled) (Harmoni, 2026)
This case study investigates the intermediary strategies employed by a local administrative authority in managing interfaith conflict within the spatially segregated residential community of Taman Kopo Indah, Bandung, Indonesia. Employing a qualitative intrinsic case study design with process tracing analysis, this research examines the de-escalation mechanisms activated following a mass congregation triggered by alleged blasphemy in a residential area characterized by demographic and religious divisions. While existing scholarship on Indonesian interfaith conflict resolution has largely centered on religious figures such as kiai and formal institutions such as the Religious Harmony Forum (FKUB), the role of secular local administrative actors as mediators within spatially segregated residential communities remains underexplored. Three primary informants were engaged: the Head of Neighborhood Unit (RW) 16, the leadership of the Persatuan Islam (Persis) Bojonghaur congregation, and the administrators of Baiturrahmaan Mosque. Drawing on Kriesberg’s Constructive Conflict theory, this case demonstrates the potential role of four tactical strategies in de-escalation: (1) Gatekeeping, which restricted external actor intervention; (2) Saving Face, through a symbolic public apology; (3) Information Filtering, by leveraging organizational command structures to halt the spread of inflammatory social media content; and (4) Re-framing, by redefining the incident as a medical rather than theological matter. This study suggests that in segregated urban spaces where formal religious mediators lack operational reach, secular local administrators may function as insider-partial mediators, offering an empirical framework for micro-level governance of religious diversity. However, the resulting stability constitutes negative peace rather than substantive interfaith integration. Abstrak Penelitian ini mengkaji strategi intermediary yang diterapkan oleh otoritas administratif lokal dalam mengelola konflik antaragama di komunitas Taman Kopo Indah yang tersegregasi secara spasial di Bandung, Indonesia. Menggunakan desain studi kasus intrinsik kualitatif dengan analisis process tracing, penelitian ini menelaah mekanisme de-eskalasi pascapengepungan massa yang dipicu dugaan penistaan agama di kawasan perumahan dengan kontras demografis dan keagamaan yang tajam. Meskipun kajian tentang resolusi konflik antaragama di Indonesia selama ini terfokus pada tokoh agama seperti kiai dan lembaga formal seperti Forum Kerukunan Umat Beragama (FKUB), peran otoritas administratif lokal yang sekuler sebagai mediator dalam komunitas perumahan tersegregasi secara spasial belum pernah dikaji secara memadai. Tiga informan utama dilibatkan: Ketua RW 16, pimpinan Jemaah Persatuan Islam (Persis) Bojonghaur, dan pengurus Masjid Baiturrahmaan. Berlandaskan teori Konflik Konstruktif Kriesberg, temuan mengungkap empat strategi taktis: (1) Gatekeeping, membatasi intervensi aktor eksternal; (2) Saving Face, melalui permintaan maaf simbolis di depan publik; (3) Penyaringan Informasi, memanfaatkan struktur komando organisasi untuk menghentikan penyebaran konten provokatif di media sosial; dan (4) Re-framing, mendefinisikan ulang insiden sebagai masalah medis, bukan teologis. Penelitian ini menyimpulkan bahwa administrator lokal sekuler dapat berperan sebagai mediator insider-partial yang efektif, menawarkan kerangka empiris tata kelola mikro keragaman beragama. Namun stabilitas yang tercipta merupakan perdamaian negatif yang dipertahankan melalui eksklusi sosial, bukan integrasi antaragama yang substantif.